Kesalahan Berbahasa dalam Penulisan di Media Sosial Kajian Sintaksis dan Semantik - Fitria Wulandari; Elisabet Simanjuntak; Piladeplia Trifosa Ginting; Raisha Mei Nabel Pakpahan; Anggia Puteri (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
Nowadays, everything has changed including the use of language. Social media certainly cannot be separated from language, because every human being will use language as communication. However, not infrequently there are still many sentence writing errors found on social media. The purpose of this article is to analyze language errors in sentences with syntactic and semantic studies. The method used is descriptive qualitative. As a result, there are still many errors found in sentences in social media. Errors in terms of syntax are found in sentence structure errors and redundant words. While in terms of semantics, inaccuracy, the use of slang, and the influence of foreign languages are factors in errors In social media. This can encourage to empowerment of grammar on social media.